Green Synthesis of Silver Nanoparticles Using Azadirachta Indica and Tinospora Cordifolia Leaves Extracts- Their Optical and Photocatalytic Study - Suvankar Saha; P. K. Mochahari (Research Aspects in Chemical and Materials Sciences Vol. 4, 2022)
Silver nanoparticles (AgNPs) have been synthesised via green route using two different plant extracts: Azadirachta indica (Neem) and Tinospora cordifolia (Giloe) leaves extracts. The formation of AgNPs has been observed from the colour change of the solution and is further confirmed by UV-Vis Spectroscopy. Optical properties of synthesized samples have been carried out using UV–VIS spectrophotometer. For Ag- A. indica NPs, the absorbance maximum occurs at 440 nm and the corresponding absorbance peak occurred at 345 nm in the case of Ag- T. cordifolia NPs. Optical band gap energy has been estimated using Tauc’s relation and variations of band gap energy at different time intervals were analysed for the AgNPs samples prepared using Azadirachta indica (Neem) as well asTinospora cordifolia (Giloe) leaves extracts. Particle size has been found to decrease with time for Ag- A. indica NPs whereas particle size increases with time for Ag- T. cordifolia NPs. The synthesized Ag NPs act as a catalyst for the degradation of methylene blue (MB) dye under visible light. The percentage of degradation was found to be 87.56% within 45 minutes of exposure to visible light.